Asked
11 months ago

Viewed
522124 times

**Answer:**

Y = 40

**Step-by-step explanation:**

44 - 66y + 65y + 5 = 9

49 - y = 9

-y = -40

y = 40

**Answer:**

y = 40

**General Formulas and Concepts:**

__Pre-Algebra__

Order of Operations: **BPEMDAS
**

- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction

- Left to Right

Equality Properties

__Algebra I__

- Combining Like Terms

**Step-by-step explanation:**

__Step 1: Define__

11(4 - 6y) + 5(13y + 1) = 9

__Step 2: Solve for ____y__

- Distribute: 44 - 66y + 65y + 5 = 9
- Combine like terms: -y + 49 = 9
- Isolate
*y*term: -y = -40 - Isolate
*y*: y = 40

__Step 3: Check__

*Plug in y into the original equation to verify it's a solution.*

- Substitute in
*y*: 11(4 - 6(40)) + 5(13(40) + 1) = 9 - Multiply: 11(4 - 240) + 5(520 + 1) = 9
- Subtract/Add: 11(-236) + 5(521) = 9
- Multiply: -2596 + 2605 = 9
- Add: 9 = 9

Here we see that 9 does indeed equal 9.

∴ y = 40 is the solution to the equation.

Enter your username or email to reset your password. You will receive an email with instructions on how to reset your password. If you are experiencing problems resetting your password contact us or send us an email